Body size variation of a high-Arctic seabird: the dovekie ( Alle alle ) - Wojczulanis-Jakubas, K.; Jakubas, D; Welcker, J.; Harding, A.M.A.; Karnovsky, N.J.; Kidawa, D.; Steen, H.; Stempniewicz, L.; Camphuysen, C.J. (Polar Biology, 2011)
Variation in body size among subpopulations of the same species may reflect phenotypic or genetic responses to environmental gradients or geographical distance. Here, we examine geographical variation in the body size of the dovekie (Alle alle), the most numerous high-Arctic seabird. Locations of dovekie breeding sites are largely restricted to the high-Arctic zone of the Atlantic. We compared wing length, head-bill length, body mass, and a body size index of 1,076 birds from nine main colonies spanning a large part of the breeding range of the species. Results suggest morphological variation across the studied populations of dovekies, with a longitudinal increase in body size from west to east. The smallest birds breed in the western part of the population (Greenland and Jan Mayen), middle-sized individuals on Svalbard, and the largest birds (A. a. polaris subspecies) breed in the eastern part of the studied area, Franz Josef Land. Environmental (air temperature, wind speed, and sea surface temperature) and geographical (intercolonial distance) parameters were analyzed to explore potential mechanisms driving differences in body size. The body size of birds increased significantly with decreasing air temperature, but only when the two subspecies were considered. We did not find a relationship between sea surface temperature and body size of birds. Also, no close relationship was revealed between birds' body size and the geographical distance between colonies. Whether the body size variation of dovekie can be explained by phenotypic plasticity in response to environmental conditions in wintering areas or a pattern of distance-independent gene flow between colonies remains to be explored.